THE STRATEGY OF ONLINE START-UP BUSINESS EXPANSION THROUGH POP-UP STORES INNOVATION - Metta Padmalia (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2014)
Entrepreneurial Marketing is a marketing activity conducted by small and medium-sized enterprises with an entrepreneurial approach. The Businessmen who able to respond market conditions quickly and anticipate market changes can be called an entrepreneurial marketer. It is very necessary, especially for start-up business that must keep innovates in order to develop brand and boost demand. Generally, start-up businesses are still not trusted by the market because of their new brand, especially for online start-up businesses which market trust is still not obtained yet. The people still not believe in it, because online start-up business doesn’t have a physical store, so they can’t see, touch or feel the product directly. These obstacles can be overcome through a pop-up store so that prospective customers can be sure before buying the product. Based on this phenomenon, researcher want to identify what is the barriers to business start-ups in developing markets. This research conducted with qualitative method by interviewing 8 project group business students at Ciputra University, Surabaya. This research has provided an entrepreneurial marketing strategy through the development of pop-up stores that fits with the needs of Ciputra University students’ business projects. Hopefully, it can be applied for business start-up to strengthen brand and increase consumer demand.